Identification and classification of risk areas in urban spaces in the South Zone of Teófilo Otoni (Research, Society and Development, 2021)
The urbanization process of cities in Brazil, in general, was influenced by economic phenomena that, as a result, promoted an unbridled urbanization without advance planning, in which numerous homes in the Brazilian territory were developed in places that did not fit the characteristics of safe housing, in this context, the southern zone of the city of Teófilo Otoni in Minas Gerais is framed. The insecurity of housing at risk is enhanced by hydrogeomorphological phenomena that, for the most part, are located in regions where the topography is unfavorable to urban development.  The risks associated with risk areas are classified into 4 increasing stages of aggressiveness, in which R1 is the mildest risk while R4 is the most aggressive risk, and for all stages there is a preventive and protective measure, and because of this it is important to have environmental studies directed at slopes, floods, landslides and others. Therefore, the behavior of the soil, in different situations, will promote the analysis as to the intensity of the degree of risk, besides helping in the process of identification and classification of the types of slides to which the analyzed areas are subjected. It is noteworthy that the southern zone of the municipality of Teófilo Otoni has a predominantly reddish-yellow latosol cover, with a marked absence of vegetation cover, which increases the possibility of geological and environmental risks.